Analisis bibliometrik: trend penelitian tentang kemampuan spasial dalam pembelajaran matematika (1994-2023) - Nurhuda Teapon; Marwa M. Sehe; Muhammad Faisal (IKIP Siliwangi, 2023)
The aim of this study was to review the landscape of leading research related to spatial skills in mathematics education from 1994 to 2023. Data were taken from the Scopus database as many as 466 and filtered to 116. The data obtained was then analyzed using bibliometric analysis with science mapping and performance techniques. Based on the results of bibliometric analysis, it can be seen that the year 2021 and 2022 has the most published articles, which are respectively 8 article. Reference tendencies related to spatial skills in mathematics education, exist 406 excellent reference in 2010. United states that it is the country that has published the most articles related to spatial abilities in mathematics learning with 49 publications and 28 links of cooperation with other countries. The focus of spatial skills research in mathematics learning leads to 1) Visualization; 2) virtual reality; 3) Mental rotation.